Determination of caffeine in DARK and Sparkling Drinks Determination of Casein in Milk. Applycation of the second derivative Spectophotometry - Rodríguez B., Angélica (2001)
It shows the use of 2nd Derivative Spectrophotometry to determine caffeine concentration in kola drinks, the direct determination is not possible due to the dark coloring, and the determination of casein in milk, a turbid sample; using for both standard addition method. The concentration of caffeine was 107ppm and 3% of casein.